Numerical investigation of the anisotropic behavior of the sand in drained condition - H. Mohamadzadeh Romiani; M.J. Saffarian; R. Zakeri; H.R. Razeghi; H. Abdeh Keykha (مهندسی عمران شریف, 2022)
The behavior of natural soils is often anisotropic. But in practice, the mechanical behavior of soils is usually assumed to be isotropic. In recent years, various constitutive models have been developed that incorporate the anisotropic behavior of soils. But most of these constitutive models cannot take into account all aspects of anisotropy. On the other hand, these models are mostly complex and several parameters are needed to be determined to define the model. Therefore, using these models in practical matters is difficult. In this study, a simple method is presented to study the anisotropic behavior of sands in drained condition. Hollow cylinder torsion tests are modeled using commercial finite element software ABAQUS. The Modified Drucker−Prager/Cap constitutive model is used to define the soil characteristics. This constitutive model is a practical model which is widely used in numerical analyses of geotechnical problems, assuming that the soil has an isotropic behavior. In order to study the effect of soil anisotropy on the shear strength and stress-strain behavior, USDFLD subroutine is used in ABAQUS software. A new subroutine, called USDANISO, was also developed that links soil mechanical parameters to the major principal stress direction in each element, separately. Therefore, when analyzing the model, soil parameters in different soil elements can change as the major principal stress direction rotates. The hollow cylinder geometry is modeled in ABAQUS software and different combinations of shear and normal stresses are applied to investigate the behavior of modeled samples under the principal stresses with different directions. In the numerical model, stress paths similar to experimental studies (hollow cylinder torsion tests), including different values of intermediate principal stress ratio, are applied to study the anisotropic behavior of soil. The results of numerical modeling are compared with the experimental results of hollow cylinder torsion tests. The obtained results show appropriate agreement with experimental studies. Nevertheless, the method, described in this study, can be an efficient and practical method to consider the effect of major principal stress direction and intermediate principal stress ratio on the mechanical behavior of sand in drained condition.